Pengembangan Aplikasi Augmented Reality Sebagai Media Pembelajaran Inovatif Untuk Meningkatkan Minat Belajar Geografi Kelas X - Muhlas Fauzi; Ninik Indawati; Yuli Ifana Sari (Universitas Pendidikan Ganesha, 2026)
Geography learning at the high school level often faces challenges in attracting students' interest in learning. Along with technological advancements, teachers are required to be more creative and innovative in delivering material so that it is easy to understand and attract students' interest. This research aims to develop Augmented Reality (AR) applications as an innovative learning medium to increase students' interest in learning in geography subjects. The method uses the Research and Development (R&D) model of Borg and Gall. Data were collected through observations, interviews, and questionnaires. The results of the study show that AR applications significantly increase students' interest in learning. Visualization of 3D models such as Characteristics of the Earth's Layer, helps students understand abstract geographical concepts. The conclusion is that Augmented Reality (AR) has great potential as an innovative learning medium for geography, because it increases students' interest and understanding.